1995
DOI: 10.2466/pms.1995.80.3c.1341
|View full text |Cite
|
Sign up to set email alerts
|

Projective Personality Tests of Children with Inflammatory Bowel Disease

Abstract: 15 children with inflammatory bowel disease were given projective tests after initial diagnosis. Analysis of responses suggested affective constriction, abandonment anxiety, and depression. The children were of good intelligence with good object relationships and psychosexual differentiation for their ages. Severe psychopathology and bizarre slippage were absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is commonly believed that Crohn's disease patients have a high prevalence of psychological disorders and may have differential personality traits. It also has been suggested that psychological disorders have a negative impact on treatment response, decreasing QoL and possibly enhancing the pathogenesis of the disease 17–26. Psychological disorders clearly relate to disease activity,27 although it remains unclear whether treatment normalizes the anxiety and depression levels in patients with Crohn's disease.…”
mentioning
confidence: 99%
“…It is commonly believed that Crohn's disease patients have a high prevalence of psychological disorders and may have differential personality traits. It also has been suggested that psychological disorders have a negative impact on treatment response, decreasing QoL and possibly enhancing the pathogenesis of the disease 17–26. Psychological disorders clearly relate to disease activity,27 although it remains unclear whether treatment normalizes the anxiety and depression levels in patients with Crohn's disease.…”
mentioning
confidence: 99%
“…Although Crohn's disease does not appear to directly affect children's cognitive abilities (Engstrom, 1992;Krall, Szajnberg, Hyams, Treem, & Davis, 1995;Szajnburg et al, 1993), the nature of the illness and the prescribed treatments may have a negative effect on children's achievement in school. Special accommodations and considerations may be required for the child or adolescent with Crohn's disease.…”
Section: Psychoeducational Implicationsmentioning
confidence: 99%
“…In adolescents, depressive symptoms have tended to follow the diagnosis of IBD (8,12,13), suggesting a relationship between depression and the IBD disease process. Projective personality testing in 15 youth with newly diagnosed IBD showed affective constriction suggestive of depression, although it was unclear if this was temporally related to IBD symptom onset (14). Although no studies have established causality, several etiologic factors have been proposed, including psychologic impact of the disease on body image or life style, difficulties adapting to physical changes induced by the disease and its treatment, direct brain effects of inflammation-related cytokines and the impact of exogenous steroids used to treat disease flares (15)(16)(17)(18).…”
mentioning
confidence: 99%